Power supply system for the helium ions linac’s injector - Anokhin, R.A.; Dubnyuk, S.N.; Gaponenko, N.І.; Zhuravlyov, V.G.; Zhuravlyov, A.V.; Zabotin, A.V.; Zajtsev, B.V.; Kravchenko, A.I.; Kobets, A.F.; Manuilenko, O.V.; Reshetnikov, V.N.; Svichenskiy, V.G.; et al. (Вопросы атомной науки и техники, 2020)
This paper presents compact power supply system for the helium ion linac’s injector. The system consists of high-voltage modulator, power supplies of cathode filament, solenoid and arc modulator. It is designed on modern semi-conductor base. Using of the designed power supply system allowed to decrease the power consumption and to get rid of spurious capacitances and pickups. As a result of improving the continuous adjustment modulator and high-voltage pulse stabilization scheme, the accelerated beam current has increased twice. Наведено опис малогабаритної системи живлення інжектора лінійного прискорювача іонів гелію, яка складається з високовольтного модулятора, блоків живлення накалу катода, соленоїда та модулятора дуги. Система виконана з використанням сучасної напівпровідникової елементної бази. Застосування розробленої системи живлення дозволило суттєво знизити енерговитрати, позбавитися паразитних ємностей та наведень. У результаті впровадження схеми стабілізації імпульсу високої напруги струм прискореного пучка збільшився в 2 рази. Приведены принципы построения и описание малогабаритной системы питания инжектора линейного ускорителя ионов гелия, состоящей из высоковольтного модулятора, блоков питания накала катода, соленоида и модулятора дуги, выполненных на современной полупроводниковой элементной базе. Применение разработанной системы питания позволило существенно снизить энергозатраты, избавиться от паразитных емкостей и наводок. Стабилизация амплитуды импульса высокого напряжения позволила увеличить ток ускоренного пучка в 2 раза.